Design and Develop Wireless Control Motorized Stage using Blynk - sanab, syahmi; Ali, Ahmad Hadi (Enhanced Knowledge in Sciences and Technology, 2022)
Motorized stage is generally a foundation to a certain application such as laser, CNC machine, 3D printing and microscope. Operational of CMS controlled by human can lead to human error and hazard while working. Application such as laser can be harmful to people that working in high power laser field. The hazardous of laser including handing the laser while micro-positioning the laser. WCMS consists of four main parts which are mechanical stage, motor driving circuit, software controller and interfacing devices. The mechanical stage was design and developed using 3D CAD and was printed using 3D printer. The material of mechanical stage is PLA plastic. The motor driver for WCMS is L298N motor driver and was used NodeMCU 2688 microcontroller for the WCMS. The system was powered by 12V 3A power supply. Smartphone is used to control the WCMS using WIFI and Blynk application was used for the interface. In order to control the WCMS, programming codes were developed by using Arduino IDE and send wirelessly via WIFI to Blynk and NodeMCU microcontroller. WCMS can be operated anywhere as long as the smartphone and the WCMS is connected to internet. As stepper motor is move, the stage of WCMS also experiencing translation. As for 1, 5, 25, 50, 100 and 200 revolution per minutes, the time taken for stage is 70, 15, 3.7, 2.2, 1.3 second, respectively.